Environmental Sound Training in Cochlear Implant Users. - Shafiro, Valeriy; Sheft, Stanley; Kuvadia, Sejal; Gygi, Brian (Journal of Speech, Language & Hearing Research, 2015)
Purpose: The study investigated the effect of a short computer-based environmental sound training regimen on the perception of environmental sounds and speech in experienced cochlear implant (CI) patients. Method: Fourteen CI patients with the average of 5 years of CI experience participated. The protocol consisted of 2 pretests, 1 week apart, followed by 4 environmental sound training sessions conducted on separate days in 1 week, and concluded with 2 posttest sessions, separated by another week without training. Each testing session included an environmental sound test, which consisted of 40 familiar everyday sounds, each represented by 4 different tokens, as well as the Consonant Nucleus Consonant (CNC) word test, and Revised Speech Perception in Noise (SPIN-R) sentence test. Results: Environmental sounds scores were lower than for either of the speech tests. Following training, there was a significant average improvement of 15.8 points in environmental sound perception, which persisted 1 week later after training was discontinued. No significant improvements were observed for either speech test. Conclusions: The findings demonstrate that environmental sound perception, which remains problematic even for experienced CI patients, can be improved with a home-based computer training regimen. Such computer-based training may thus provide an effective low-cost approach to rehabilitation for CI users, and potentially, other hearing impaired populations.